A case study on the effectiveness of teaching language games in motivating the learners of english / Norhida Anuar - Anuar, Norhida (2002)
The purpose of this case study was to find out the use of the language games in motivating the learners of English. A pre-test and post-test had been conducted on the Experimental Group and Controlled Group in this study. In addition, a short questionnaire was administered to find out the pupils and teachers opinions on the use of language games in the teaching and learning process. The findings of this study revealed that the controlled group has performed better than the Experimental Group. However, if we look at the raw score, the Experimental Group had managed to make a slight improvement in their posttest scores. This means that language games have certain degree of influence on the pupils’ academic performance.